Contributing factors to adoption of electronic medical records in otolaryngology offices. (31st May 2013) - Mahboubi, Hossein; Salibian, Ara A.; Wu, Edward C.; Patel, Madhukar S.; Armstrong, William B.
Abstract : Objectives/Hypothesis: (1) To determine the characteristics of outpatient otolaryngology offices with an electronic medical record (EMR) system, and (2) to compare those characteristics with the trends in surgical and medical specialties. Study Design: Cross‐sectional analysis of U.S. representative data from the National Ambulatory Medical Care Survey (NAMCS). Methods: The 2005 to 2010 NAMCS datasets were analyzed. Physicians' specialty was recoded as otolaryngology, all surgical specialties, and all specialties combined. Physician offices with all‐ or partial‐EMR system adoption were then compared to offices without EMR systems with respect to year; geographic region; urban setting; office setting; practice type; practice ownership; employment status; and revenues from Medicare, Medicaid, private insurance, and patient payment. Results: Upon univariate analysis, EMR use was significantly higher among otolaryngology practices located in metropolitan areas and practices run or owned by larger groups of practitioners. Sources of patient revenue did not correlate with the likelihood of EMR use. Multivariate analysis revealed that EMR use by otolaryngologists was significantly associated with group practices and offices owned by institutions. Similar associations were observed with surgical specialties combined in addition to a higher EMR usage in practices with more than 25% of total revenue from private insurance. Conclusions: EMR utilization by otolaryngology practices appears similar to that of other specialties, and is more likely in metropolitan areas and larger practice settings. Despite the announcement of incentive programs under Medicare and Medicaid in 2009, EMR usage was not dependent on the percentage of physicians' total revenue from these sources. Level of Evidence: N/A. Laryngoscope, 123:2658–2663, 2013